Namesakes or relatives? Approaches to investigating the relationship between Y chromosome haplogroups and surnames - Balanovska, E. V.; Romanov, A. G.; Balanovsky, O. P. (Molecular biology (New York), 2011)
Population genetics successfully applies surnames as quasi-genetic markers when estimating similarity between populations and calculating the level of random inbreeding. These calculations are based on the isonymy coefficient, which assumes that every surname is monophyletic, i.e., it originated from a single common ancestor and all namesakes are therefore relatives. On the other hand, there is a general opinion that a typical Russian surname is polyphyletic: it originated multiple times and most namesakes are, therefore, not related to each other. Combined studies of Y chromosomes and surnames now allow us to address this issue. This study discusses approaches to statistical evaluation of Y chromosome haplogroup frequencies in groups of people bearing the same surname (namesakes). The proposed index of accumulated haplogroup frequency eliminates the artifactual effect of a randomly increased haplogroup frequency in namesakes by subtracting its population (expected) frequency from the observed value, while the expected frequency is calculated as the weighted average of the frequencies of this haplogroup in the populations where the surname carriers come from. From the total sample (comprising 1244 persons from 13 populations of the historical Russian area), 123 individuals carrying 14 most frequent surnames were chosen. A comparison of the haplogroup frequencies in these 14 namesake groups and in 14 respective population control groups compiled from the total sample showed that accumulation of certain Y chromosome haplogroups was nonrandom even in carriers of widespread surnames. An analysis of Y-STR haplotypes rather than Y-SNP haplogroups could provide a better insight into relationships between namesakes and will be the subject of further research.